OP0209 Genetic variance in IL2RA associates with progression of joint destruction and circulating SIL-2RA levels in rheumatoid arthritis. (23rd January 2014) - Knevel, R.; de Rooy, D.; Zhernakova, S.; Gröndal, G.; Krabben, A.; Steinsson, K.; Cavet, G.; Toes, R.; Huizinga, T.; Gregersen, P.; van der Helm-van Mil, A.
Abstract : Background: Since most therapeutic strategies are targeted to affect pathways of disease progression, interrogation of the genome with disease progression as an outcome is attractive. At this moment, 32 regions have been associated with RA susceptibility and 20 of these loci have been tested for an association with joint destruction. Objectives: In the current study, we investigated the remaining 12 susceptibility loci for their association with rate of joint destruction. Methods: The associations of the 12 susceptibility loci ( AFF3, ANKRD55, BLK, CCL21, CTAL4, IL21, IL2RA, IL2RB, IRF5, REL, SPRED2 and STAT4 ) with the rate of joint destruction were tested in 596 Dutch patients with yearly X-rays during 7 follow-up years. Significant associations were subsequently tested in three additional cohorts from the USA and Iceland. Results were combined in a meta-analysis, consisting of 7, 732 X-rays of 1, 750 patients in total. X-rays of all cohorts were scored according to the Sharp-van der Heijde Score by Dutch trained scorers (all ICCs>0.9). The locus associated with rate of joint destruction ( IL2RA ) was further studied with serum levels (sIL-2RA) measured with ELISA. Finally the region of the identified SNP was fine-mapped using the ImmunoChip platform. Results: In the discovery cohort, an association with rate of joint destruction was found for AFF3 (p=2.8×10 -2 ), BLK (p=3.1×10 -2 ) and IL2RA (p=4.4×10 -3 ). Of these, the minor allele of Il2RA (rs2104286) was associated with a lower rate of joint destruction in the meta-analysis (p=7.2×10 -4 ). Furthermore, the IL2RA minor allele was associated with a 0.85-fold change in circulating levels of soluble IL-2RA (p=1.0×10 -3 ). In addition, lower sIL-2RA level was associated with a lower rate of joint destruction per year (p=4.2×10 -3 ). The association of IL2RA with rate of joint destruction was further focused to a region of 40kb encompassing the IL2RA intron 1 and the 5' region of IL2RA and RBM17 . Conclusions: We found an association of IL2RA with rate of joint destruction and supported this with the association of IL2RA with sIL-2RA in serum. The present results comprising high-quality phenotypic outcome data, genotyping, fine-mapping and serologic data, support the role of IL2RA in severity of progression of RA. Acknowledgement: The authors acknowledge deCODE Genetics for providing the genetic and genealogic data. Specifically we want to thank Ari Kárason and Stacy Steinberg for their assistance in the logistics and the analyses. Disclosure of Interest: R. Knevel: None Declared, D. de Rooy: None Declared, S. Zhernakova: None Declared, G. Gröndal: None Declared, A. Krabben: None Declared, K. Steinsson: None Declared, G. Cavet Grant/Research support from: Crescendo Bioscience measured sIL2RA levels, R. Toes: None Declared, T. Huizinga: None Declared, P. Gregersen: None Declared, A. van der Helm-van Mil: None Declared